Plasma levels of apolipoprotein E and risk of dementia in the general population - Rasmussen, Katrine L.; Tybjærg-Hansen, Anne; Nordestgaard, Børge G.; Frikke-Schmidt, Ruth (Annals of neurology, 2015)
Objective The apolipoprotein E (APOE) ε4 allele is a major genetic risk factor for Alzheimer disease and dementia. However, it remains unclear whether plasma levels of apoE confer additional risk. We tested this hypothesis. Methods Using 75,708 participants from the general population, we tested whether low plasma levels of apoE at study enrollment were associated with increased risk of future Alzheimer disease and all dementia, and whether this association was independent of ε2/ε3/ε4 APOE genotype. Results Multifactorially adjusted hazard ratios (HRs) for Alzheimer disease and all dementia increased from the highest to the lowest apoE tertile (p for trends < 1 × 10−6). Multifactorially adjusted HRs for lowest versus highest tertile were 2.68 (95% confidence interval [CI] = 2.04–3.52) and 1.80 (95% CI = 1.52–2.13) for Alzheimer disease and all dementia, respectively. After further adjustment for ε2/ε3/ε4 APOE genotype, plasma apoE tertiles remained associated with Alzheimer disease (p for trend = 0.007) and all dementia (p for trend = 0.04). Plasma apoE tertiles did not interact with ε2/ε3/ε4 APOE genotype on risk of Alzheimer disease (p = 0.53) or all dementia (p = 0.79). In a subanalysis, the −219G>T GT promoter genotype, associated with low plasma apoE levels, remained significantly associated with increased risk of Alzheimer disease after adjustment for ε2/ε3/ε4 APOE genotype (HR = 1.56, 95% CI = 1.05–2.30). Interpretation Low plasma levels of apoE are associated with increased risk of future Alzheimer disease and all dementia in the general population, independent of ε2/ε3/ε4 APOE genotype. This is clinically relevant, because no plasma biomarkers are currently implemented. Hence, plasma levels of apoE may be a new, easily accessible preclinical biomarker. Ann Neurol 2015;77:301–311